Basics Fashion Photo Editing Module for Fashion Design Students Based on Indonesian National Work Competency Standards - Julian Prio Dwi Nugroho; Mohammad Adam Jerusalem (Jurnal Pendidikan Indonesia, 2023)
The limitations of the learning media on fashion photo editing materials become the main obstacle to achieving basic digital photo editing competence in the Fashion Photography course. Therefore, it is necessary to develop relevant modules. This study aims to develop an SKKNI-based basics fashion photo editing module for fashion students that can be used in the learning activities of fashion photography. This study is a research and development conducted using the ADDIE model. The subjects of this study were 30 students of the Fashion Design Study Program. The data were obtained from product evaluation by material experts and media experts as well as field trials involving research subjects. These data were analyzed using descriptive quantitative techniques. The result of this study is a basic module for fashion photo editing based on the basic digital photo processing competency sub-unit materials in the Indonesian National Work Competency Standards of Photography. From the material aspect, the developed module was considered valid (0.85) and reliable (0.742). The media aspect of the module was also regarded as valid (0.82) and reliable (0.714). Thus, it can be concluded that the module developed was of expert quality and feasible to use. Based on the percentage of students achieving the minimum passing grade, the developed module is categorized as effective (80%) as a learning media in the basic materials of fashion photo editing.